1992
DOI: 10.2190/ah7v-fpm6-prdx-fnqe
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Contexts of Red Ochre Use in Paleoindian and Upper Paleolithic Sites

Abstract: Red ochre is one of nine traits common to Paleoindian and Upper Paleolithic complexes. The similarity goes beyond simple presence, however, and encompasses virtual identity of the context in which ochre appears. These include burials, non-mortuary ritual context, and domestic context. Data are assembled here comparing the use of ochre in each context in the Upper Paleolithic and the Paleoindian periods. Particular attention is given to the Upper Paleolithic sites in the Soviet Union and the Paleoindian sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Whereas symbolic readings (e.g., Knight, 1991;Knight et al, 1995;Power, 2001;Power and Aiello, 1997;Power and Watts, 1997;Watts, 1999Watts, , 2002Watts, , 2009 draw largely from ethnographic (Bleek and Lloyd, 1911;Marshall, 1961Marshall, , 1976Viegas Guerreiro, 1968) and historical accounts (Campbell, 1815;Burchell, 1822;Methuen, 1846;Stow, 1905;Silberbauer, 1965), functional interpretations (e.g., Keeley, 1980;Velo, 1984;Roper, 1991;Mahaney et al, 2000;Riel-Salvatore and Clark, 2001;Wadley et al, 2004Wadley et al, , 2009Lombard, 2007;Arocena et al, 2008;Prinsloo et al, 2008;Chambers, 2010) derive mainly from archaeological evidence and experimental results.…”
Section: Archaeological Ochrementioning
confidence: 99%
“…Whereas symbolic readings (e.g., Knight, 1991;Knight et al, 1995;Power, 2001;Power and Aiello, 1997;Power and Watts, 1997;Watts, 1999Watts, , 2002Watts, , 2009 draw largely from ethnographic (Bleek and Lloyd, 1911;Marshall, 1961Marshall, , 1976Viegas Guerreiro, 1968) and historical accounts (Campbell, 1815;Burchell, 1822;Methuen, 1846;Stow, 1905;Silberbauer, 1965), functional interpretations (e.g., Keeley, 1980;Velo, 1984;Roper, 1991;Mahaney et al, 2000;Riel-Salvatore and Clark, 2001;Wadley et al, 2004Wadley et al, , 2009Lombard, 2007;Arocena et al, 2008;Prinsloo et al, 2008;Chambers, 2010) derive mainly from archaeological evidence and experimental results.…”
Section: Archaeological Ochrementioning
confidence: 99%
“…From the Upper Paleolithic record, red ochre is indeed well known for its use in cave paintings and in ritual burial contexts. More "mundane" or "domestic" uses of red ochre (derived from hematite, Fe 2 O 3 ) are known from the ethnographic record of modern hunter-gatherers, for instance, as (internal and external) medication, as a food preservative, in tanning of hides, and as insect repellent (3)(4)(5)(6)(7)(8)(9). Archeological studies have identified ochre powder as an ingredient in the manufacture of compound adhesives (10).…”
mentioning
confidence: 99%
“…It has been described as medicinally useful (Mahaney et al, 1993;Velo, 1984Velo, , 1986, symbolically charged (Marshack, 1981;Taçon, 2004), functionally valuable as a filler for adhesive (Lombard, 2005;Wadley, 2005), a preservative (Roper, 1991;Wadley, 2005), as well as pigment for rock art, as house floor deposits, as wall painting or pottery decoration, and in association with burials (Roper, 1991).…”
Section: Brief Review Of Ochre Researchmentioning
confidence: 99%